Mnemonic Techniques in Foreign Language Acquisition: Efficacy Analysis - Banerjee, Soumen (Journal of Educational Research and Policies, 2025)
Mnemonics, as a technique for improving the effectiveness of learning foreign languages, is based on the creation of stable associative links that facilitate memorization and integration of new material into long - term memory. The main purpose of this approach is to activate the cognitive resources of the student for the rapid development of vocabulary, grammar, and speech structures through the use of vivid visual and verbal associations. The methodological basis for considering the topic was the experiments of other researchers demonstrating the influence of mnemonics in improving the effectiveness of teaching foreign languages. Also, as part of the work, the literature that is in the public domain was studied. The analysis of the sources showed that the use of mnemonics leads to a significant reduction in the time required to master and consolidate language material, as well as to an increase in motivation due to the fascination of the process. The use of visual associations, such as color coding grammatical structures or creating visual images for words, strengthens long - term memory and helps to maintain high student interest. In conclusion, it can be argued that mnemonic techniques can act as an effective tool for intensifying the process of learning foreign languages, helping to overcome cognitive barriers, and reducing stress associated with memorizing a large amount of information.